TSLP pretreatment inhibits M1 macrophage polarization and attenuates LPS-induced iNKT cell-dependent acute lung injury - Zhou, Ting; Zhang, Ziyao; Zhan, Yawen; Wang, Meiying; Wu, Mi; Weng, Xiufang; Xu, Younian (Frontiers in Immunology, 2025)
IntroductionSepsis associated acute respiratory distress syndrome (ARDS), is a life-threatening condition characterized by severe pulmonary inflammation. Previous research has suggested that allergic immune diseases are associated with a lower risk of sepsis. Therefore, we hypothesized that certain molecules involved in type 2 inflammation are beneficial for the outcome of sepsis associated ARDS. Thymic stromal lymphopoietin (TSLP) is known to promote Th2 responses in allergic disease, however, its role in sepsis associated ARDS remains limited.MethodsTo investigate the role of TSLP in sepsis associated lung injury, we administered exogenous recombinant TSLP to wild-type mice, followed by lipopolysaccharide (LPS) challenge. At 24 hours post-treatment, bronchoalveolar lavage fluid (BALF) and lung tissues were collected for analysis. The ratio, number, phenotype, and function of immune cells and cytokine levels were measured. Additionally, murine bone marrow-derived macrophages (BMDMs) were prepared and stimulated with LPS and TSLP to further verify our findings experimentally. To explore the molecular mechanisms of TSLP’s effect, analysis of transcriptome sequencing and single-cell transcriptome sequencing and subsequent experiments were performed.ResultsIn LPS-induced acute lung injury models, pretreatment with TSLP significantly alleviated lung injury, suppressed inflammatory cytokines secretion, and reduced macrophages and neutrophils infiltration. In addition, TSLP treatment significantly inhibited M1 macrophage polarization and promoted M2 macrophage differentiation. Transcriptome sequencing suggested IFN-γ as a potential target of TSLP, and single-cell transcriptome sequencing showed that innate like T cells are important source of IFN-γ. Consistently, flow cytometry showed that proportion of IFN-γ-producing iNKT cells was decreased by TSLP administration in the acute lung injury model. Intriguingly, Jα18−/− mice, which are completely deficient in invariant natural killer T (iNKT) cells, exhibited not only significantly less severe lung inflammation but also a notably higher degree of anti-inflammatory Arg1+ M2 macrophages infiltration when compared with their LPS-sensitized wild-type counterparts.ConclusionsThese findings not only underscore the crucial role of TSLP in the regulation of sepsis-associated ARDS but also demonstrate its potential clinical value as both a predictive biomarker for early detection and a molecular target for therapeutic intervention.